Rosin from Pinus pinaster Portuguese forests shows a regular profile of resin acids - Pinheiro, Ângela; Martins, Isabel; Bento, Artur; Escórcio, Rita; Nunes, Carolina; Varela, Adélia; Nunes, João; Afonso, Carlos A.M.; Silva Pereira, Cristina (Frontiers in Plant Science, 2023)
Pinus pinaster forestry occupies >20% of the forest ecosystem area in the continental territory of Portugal with a high impact on the national economy. This species' major derived non-wood product is oleoresin; the raw material for rosin production. Rosin comprises mainly a blend of resin acids and has broad industrial and pharmaceutical applications. Oleoresin production in Portugal has been progressively reduced due to low-cost producers in other countries; currently, it reaches only 2% of the existent P. pinaster trees. To support this value chain, the chemical fingerprint of rosin derived from the national forest requires focused analysis. In the present study, we collected oleoresin within seven geographically distinct pure P. pinaster forests, in two consecutive collection years. A highresolution NMR method was used to quantify the diversity of resin acids in the corresponding rosin samples. Overall, the acquired data highlighted that the profile of resin acids in P. pinaster rosin produced in Portugal is highly regular, regardless of the forest location, having as the major constituents abietic acid and dehydroabietic acid. The diversity of resin acids is possibly influenced, to a minor extent, by some edaphoclimatic factors.